2016
DOI: 10.1007/s00253-016-7816-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced extracellular production of L-asparaginase from Bacillus subtilis 168 by B. subtilis WB600 through a combined strategy

Abstract: L-asparaginase (EC 3.5.1.1, ASN) exhibits great commercial value due to its uses in the food and medicine industry. In this study, we reported the enhanced expression of type II ASN from Bacillus subtilis 168 in B. subtilis WB600 through a combined strategy. First, eight signal peptides (the signal peptide of the ASN, ywbN, yvgO, amyE, oppA, vpr, lipA, and wapA) were used for ASN secretion in B. subtilis by using Hpa II promoter, respectively. The signal peptide wapA achieved the highest extracellular ASN acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 32 publications
1
56
0
Order By: Relevance
“…In this study, P 43 showed the best effect on improving the transcription level of L-asparaginase gene throughout the exponential phase and the early stationary phase (Figures 3 and 4), and the transcription level and protein expression level are not directly correlated (Figure 1). These results are in accordance with the previous reports [12,49]. Further, we found that the secondary structures in RBS regions, which were caused by mismatch between the promoter and RBS, were the reason of the inconsistent enzyme production with transcription levels, so an appropriate RBS sequence that improved the rate of translation was key to further enhance enzyme production.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, P 43 showed the best effect on improving the transcription level of L-asparaginase gene throughout the exponential phase and the early stationary phase (Figures 3 and 4), and the transcription level and protein expression level are not directly correlated (Figure 1). These results are in accordance with the previous reports [12,49]. Further, we found that the secondary structures in RBS regions, which were caused by mismatch between the promoter and RBS, were the reason of the inconsistent enzyme production with transcription levels, so an appropriate RBS sequence that improved the rate of translation was key to further enhance enzyme production.…”
Section: Discussionsupporting
confidence: 93%
“…However, the low yield of L-asparaginase has restricted the application of this enzyme in the food and pharmaceutical industries. A series of strategies have been used to improve L-asparaginase production, such as optimization of fermentation medium and process [9][10][11], signal peptide screening, promoter mutation, and N-terminal deletion [12]. To date, the highest yield of L-asparaginase obtained was 2168 U/mL, which was reported in our previous work [13].…”
Section: Introductionmentioning
confidence: 68%
“…Transcriptional analysis of ecglmS was conducted as described by Feng et al Total RNA was extracted using the RNAisoPlus kit (TaKaRa, Dalian, China), and used to synthesize the cDNA using the PrimeScript RT reagent Kit Perfect Real Time (TaKaRa Bio‐Inc, Otsu, Shiga, Japan). Quantitative PCR (qPCR) was conducted by a LightCycler 480 II Real‐time PCR instrument (Roche Diagnostics, Mannheim, Germany) using a SYBR Premix Ex Taq Kit (TaKaRa).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous examples on the optimization of heterologous enzyme production in B . subtilis have been published – which attempt to improve the overall process efficiency, finding new interesting enzymes and to develop more suitable chassis for the industry (Chen et al ., ; Feng et al ., ).…”
Section: Bacterial Species Adopted As a Chassis: From Historical Exammentioning
confidence: 99%
“…Some examples of industrially relevant enzymes produced in B. subtilis chassis are subtilisin (an alkaline serine protease), aand b-amylases, b-glucanases and laccases (Schallmey et al, 2004). Numerous examples on the optimization of heterologous enzyme production in B. subtilis have been publishedwhich attempt to improve the overall process efficiency, finding new interesting enzymes and to develop more suitable chassis for the industry Feng et al, 2017). Apart from its prominent role in protein production, B. subtilis is also used for industrial processes aimed at the synthesis of nucleotides, vitamins, surfactants and antibiotics, for example bacitracin and subtilin.…”
Section: Bacillus Subtilismentioning
confidence: 99%